Linear instability of asymmetric Poiseuille flows - Kachuma, D; Sobey, I (Oxford University Computing Laboratory, 2007)
We compute solutions for the Orr-Sommerfeld equations for the case of an asymmetric Poiseuille-like parallel flow. The calculations show that very small asymmetry has little effect on the prediction for linear instability of Poiseuille-like flow but that moderate asymmetry, such as found in channel flow near an elongated wall vortex, has a large effect and that instability can occur at much lower (less than 100) Reynolds numbers. We give some characterisation of the instability.